Combination of interleukin-6 and C-reactive protein levels as predictive biomarkers for early diagnosis of community-acquired pneumonia in ICU patients - Ramly, Nur Fariza; Lee, Kam Wah; Nanyan, Suhaila; Abdul Ghani, Muhamad Rasydan; Ab. Rashid, Iqbalmunauwir (Faculty of Anaesthesia, Pain and Intensive Care, Aga Khan University Hospital, 2025)
Background & objective: Pneumonia is a leading cause of morbidity and mortality globally, accounting for 15.2% of deaths in Malaysia in 2023. Community-acquired pneumonia (CAP) poses diagnostic challenges due to the non-specificity of clinical presentations and inconsistencies in imaging interpretation. This study evaluates the diagnostic utility of biomarker interleukin-6 (IL-6), C-reactive protein (CRP) and procalcitonin (PCT), individually and in combination, to improve the diagnosis of CAP in critically ill patients. Methodology: This prospective cohort study was conducted in an intensive care unit. Adult patients admitted with dyspnea and respiratory failure were recruited, with 33 patients classified as CAP by standardized definition, and 42 as non-CAP. Biomarker levels were assessed in both groups, and diagnostic performance was evaluated with optimum cutoff levels. Results: Individually, IL-6, CRP and PCT showed poor diagnostic accuracy (AUC < 0.7). The IL-6 and CRP combination achieved the highest AUC (0.759, sensitivity 78%, specificity 67%). The IL-6 and PCT combination provided the highest sensitivity (91%) and negative predictive value (85%), aiding in ruling out CAP. Conclusion: Combined biomarker evaluation enhances diagnostic accuracy for community-acquired pneumonia, providing a basis for early treatment. These findings warrant further multicenter validation to confirm their clinical applicability in community-acquired pneumonia diagnosis.